Vasoactive-inotropic score for prediction of critical patient mortality: A systematic review - Umarmono, Umarmono; Purnawan, Iwan (Malahayati International Journal of Nursing and Health Science, 2025)
Background: A medical emergency is a clinical situation that requires immediate and planned treatment to prevent permanent disability or death. It involves sudden, progressive, and often life-threatening disturbances in vital body functions, such as cardiovascular, respiratory, or neurological disorders. The Vasoactive-Inotropic Score (VIS) is a clinical tool used to assess the need for vasoactive and inotropic drugs in critically ill patients. The VIS plays an important role as a prognostic indicator in critically ill patients, with higher VIS scores associated with increased risk of death. Purpose: To evaluate vasoactive-inotropic score for prediction of critical patient mortality. Method: A literature review with the aim of reviewing and evaluating previous research related to the use of VIS in predicting mortality in medical emergency patients using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flow diagram method. The search for scientific articles was conducted in October-November 2024 by determining the population/problem, intervention, comparison, and outcome (PICO) method. The database search process was carried out through the Publish or Perish application from PubMed, Scopus, Crossref, Semantic Scholar, and CINAHL. Determination of the article year range was focused on articles from 2018-2024 through keywords consisting of ''inotrope'' AND ''predictor'' AND ''mortality'', ''VIS'' AND ''Patient critical ill'', ''VIS'' OR Predictor mortality, ''VIS'' OR ''ICU''. Results: The Vasoactive-Inotropic Score (VIS) is an effective and practical clinical tool to be used as a predictor of mortality in emergency and critical patients. VIS provides a quantitative picture of the severity of hemodynamic disorders as well as the pharmacological need to maintain the patient's cardiovascular stability. Its use has been shown to be significant in a variety of critical conditions, such as postoperative cardiac surgery, cardiogenic shock, sepsis, and out-of-hospital cardiac arrest, where higher VIS values are often correlated with an increased risk of mortality. The accuracy of VIS in predicting mortality risk can be improved through integration with other clinical parameters, such as inflammatory biomarkers and organ dysfunction scores, which provide a more comprehensive picture of the patient's physiological status. Conclusion:  VIS is consistently used as a predictive tool with varying morbidity-mortality thresholds in critically ill patients depending on population size. Factors that influence VIS values ​​include patient demographic characteristics, hemodynamic status, disease severity, and quality of therapy received by the patient.